Assessing Compliance with Domestic Waste Disposal Practices: Insights from Cagayan de Oro City - Araune, Paolo; Vera, Glenda De; Gales, Trixie; Guibao, Ralph Jehnisan; Jaducana, Serra Abigail; Jamero, Caine Derick; Juan, Chelsea; Lagrito, Claudette Jerace; Maglinte, Princess Lettice; Maulion, Patricia Isabelle; Monte, Crystal Angela; Pascual, Sermae Angelina; Pulmones, Romeo Renz (International Journal of Nursing and Health Services (IJNHS), 2024)
Background & Aim: Domestic waste, encompassing various types like food, recyclable, garden, and hazardous waste, poses significant challenges in rapidly urbanizing areas like Cagayan de Oro City. This study aimed to assess compliance with domestic waste disposal practices in a selected barangay, focusing on proper disposal, segregation, and reuse. Methods & Materials: A descriptive research design was employed to evaluate compliance with domestic waste disposal practices among Cagayan de Oro City barangay residents. Surveys were conducted with randomly selected respondents aged 20 to 65, covering waste disposal, segregation, and reuse. Stratified random sampling ensured proportional representation from various zones within the barangay, with a sample size of 349 respondents determined using Cochran's formula. Results: Significant differences were found in compliance based on age and gender, with middle-aged individuals and females showing higher levels, especially in reuse. Employment status significantly influenced compliance, with retirees and the unemployed exhibiting higher levels compared to employed. No significant differences were observed based on education, socio-economic status, or information source. Conclusion: Gender and employment significantly influenced compliance, with men showing greater disposal compliance and women demonstrating higher adherence to segregation and reuse. Age also played a notable role, particularly in influencing reuse practices. Targeted interventions considering these factors are essential for enhancing waste management strategies. Recommendation: Clinical practitioners should focus on tailored waste disposal programs to improve compliance with domestic waste disposal practices, emphasizing the importance of proper segregation, reuse, and disposal techniques to foster cleaner and healthier communities in rapidly urbanizing areas.